Puntos fuertes y débiles de las cooperativas desde un concepto amplio de gobierno empresarial - autor, Sin (REVESCO. Revista de Estudios Cooperativos, 2008)
This paper discusses the frequent consideration of the cooperativism as disadvantageous model regard to other forms of business organization. However, the economic analysis allows to differentiate the most idiosyncratic aspects of the co-operatives, which are (they have to be) organizations of participation, since his associates are, simultaneously, capitalists and users of the business activity. Therefore, the associates have double interest in which his companies work according to the targets that motivated the economic affiliation. This phenomenon is named a identity principle or cooperative tie. The business government is the set of all the ways of taking part, directly (take decisions) or indirectly (economic and financial activity), so that the identity principle is supported. The text ends up by underlining an apparent paradox: the least competitive co-operatives would be those that only sound of name, the uncontrollable ones, those where the identity principle is not respected.
Keywords: Cooperativism in fact; Economic analysis; Participation; Competitiveness; Government